2013
DOI: 10.1107/s0907444913001923
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of malaria-parasite lysyl-tRNA synthetase provides a platform for drug development

Abstract: Aminoacyl-tRNA synthetases are essential enzymes that transmit information from the genetic code to proteins in cells and are targets for antipathogen drug development. Elucidation of the crystal structure of cytoplasmic lysyl-tRNA synthetase from the malaria parasite Plasmodium falciparum (PfLysRS) has allowed direct comparison with human LysRS. The authors' data suggest that PfLysRS is dimeric in solution, whereas the human counterpart can also adopt tetrameric forms. It is shown for the first time that PfLy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 34 publications
5
88
0
Order By: Relevance
“…To fulfill the requirements of protein synthesis, malaria parasite protein translation enzymes and their reaction substrates and products need to be distributed between apicoplasts, mitochondria, and cytoplasm (7,8,13,14,22). In P. falciparum, dual localization of single-copy aaRSs has been observed in the cases of Ala-RS, Gly-RS, Thr-RS, and Cys-RS (7,8,13,14,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfill the requirements of protein synthesis, malaria parasite protein translation enzymes and their reaction substrates and products need to be distributed between apicoplasts, mitochondria, and cytoplasm (7,8,13,14,22). In P. falciparum, dual localization of single-copy aaRSs has been observed in the cases of Ala-RS, Gly-RS, Thr-RS, and Cys-RS (7,8,13,14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Malaria parasite aaRSs are currently being explored as new targets for drug development (22,23). Within aaRSs, MRSs can serve as valuable drug targets because of their sequence and domain heterogeneity.…”
mentioning
confidence: 99%
“…One early study reported aaRS activity in P. berghei cell-free extracts (89), and genome sequencing later revealed the entire complement of aaRSs in Plasmodium (10,68,88). But to date, cytoplasmic and apicoplast P. falciparum aspartyl-tRNA synthetase (28,29), lysyltRNA synthetase (30,31), and tryptophanyl-tRNA synthetase (32,33) are the only other malarial aaRSs besides PfGluRS to be functionally or structurally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Mupirocin, for example, is a topical antibiotic already in clinical use, and other aaRS inhibitors such as the boronated antifungal compound AN2690 (27) are being developed. Aminoacylation in malaria parasites had been little studied despite its critical role in parasite biology and potential as a drug target, but studies describing the apicoplast (28) and cytoplasmic aspartyl-tRNA synthetases (29), lysyl-tRNA synthetases (30,31), and tryptophanyl-tRNA synthetases (32,33) were recently published.…”
mentioning
confidence: 99%
“…Ap4A hydrolase in the parasite hints at a special role for this molecule in parasite physiology. [9,10] Sulfonamides represent an important class of medically important compound, which is present in a number of biologically active molecules. In addition, sulfonamide derivatives are extensively used as antitumor, [11,12] antiviral, [13] antimalarial, [14,15] anti-inflammatory, [16] anticancer, [17] anti-carbonic anhydrase, [18] antidiabetic agents, [19] and in Alzheimer's diseases.…”
Section: Introductionmentioning
confidence: 99%